Predictors of Adolescents' Psychological Distress and Internet Addiction: the Role of Interpersonal Stress and School Burnout. - Zhang, Xinwen; Li, Chunkai (Journal of Child & Family Studies, 2024)
Adolescence is a critical period characterized by more frequent interpersonal interactions, which may lead to inevitable interpersonal stress. Given the negative impacts of interpersonal stress on adolescents' development, this study attempts to explore how interpersonal stress might influence psychological distress and Internet addiction among Chinese adolescents. 1278 middle and high school students aged 12–18 years old participated in this study. The results showed a positive direct effect of interpersonal stress on psychological distress, as adolescents exposed to a higher level of interpersonal stress were found to have more psychological distress. This direct effecting path was mediated by school burnout. Additionally, the relationship between interpersonal stress and Internet addiction was also mediated by school burnout. This study provides insight into how interpersonal stress affects psychological and behavioral outcomes among Chinese adolescents. The findings could guide policymakers and professional counselors involved with adolescents struggling to treat psychological distress and Internet addiction. Highlights: There is a lack of understanding as to the underlying mechanisms of how interpersonal stress leads to negative outcomes. This study extended the analysis of Chinese literature beyond academic stress to include diverse sources of interpersonal stressors in adolescents. This study established a comprehensive framework in which school burnout mediated the association between interpersonal stress and adolescents' psychological distress. This study demonstrated a framework in which school burnout mediated the relationship between interpersonal stress and Internet addiction.